2007
DOI: 10.1016/j.archoralbio.2007.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cell lines that exhibit pluripotency from miniature swine periodontal ligaments

Abstract: ObjectiveThe periodontal ligament (PDL) is a fibrous connective tissue composed of heterogeneous cell types, including PDL fibroblasts. It is not clear whether cells within the PDL fibroblast population retain the potency to differentiate into other cell types. DesignIn the present study, clonal cell lines, derived from Clawn miniature swine PDLs, were established by gene transfection for a human telomerase reverse transcriptase, and characterized. ResultsThese cell lines, denoted TesPDL1-4, had PDL fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…It has been demonstrated that many genes trigger oncogene-induced senescence in vitro and in vivo [49]. Periostin has been shown to be highly expressed in immortalized human microvascular endothelial cells [50] and TesPDL cells, derived from miniature swine periodontal ligaments [51], where these cells are transfected with hTERT to prevent cell senescence. However, there are no reports on the direct role of periostin as an oncogene product that results in the unlimited replicative potential of cancer cells.…”
Section: Limitless Replicative Potentialmentioning
confidence: 99%
“…It has been demonstrated that many genes trigger oncogene-induced senescence in vitro and in vivo [49]. Periostin has been shown to be highly expressed in immortalized human microvascular endothelial cells [50] and TesPDL cells, derived from miniature swine periodontal ligaments [51], where these cells are transfected with hTERT to prevent cell senescence. However, there are no reports on the direct role of periostin as an oncogene product that results in the unlimited replicative potential of cancer cells.…”
Section: Limitless Replicative Potentialmentioning
confidence: 99%
“…We previously showed that a swine PDL fibroblast cell line, namely, TesPDL3, could express EC markers and osteoblast markers in addition to PDL markers (9,10 that construct blood vessels with a mature lumen by evaluating their ability to vascularize in a 3-dimensional type I collagen scaffold. We established several single cell-derived cultures (SCDCs) from a primary culture of rat PDL fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…2a). On the other hand, SCDCs consistently expressed mRNAs for extracellular matrix proteins of PDL, that is, α1(I) procollagen, OPN and periostin [15], although slight differences in their expression levels were observed (fig. 2b).…”
Section: Resultsmentioning
confidence: 99%
“…The PDL cell line, TesPDL, was established by over-expression of human telomerase reverse transcriptase (hTERT) in cells derived from swine PDL [15]. However, we cannot exclude the possibility that hTERT itself affects the expression of mesenchymal stem cell-like activity in cells derived from PDL.…”
Section: Introductionmentioning
confidence: 99%